Educational Values in the Story of Nūh AS in the Qur'an - Amrah Kasim, Ahmad Wakka, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research departs from the desire to reveal the story of Prophet Nūh and the values of Islamic education in the story of Prophet Noah as. The main problem in this research is "educational values in the story of Noah in the Qur'an in the Surahs Hūd, Nūh, and al-Mu'minun in the Qur'an by using thematic methods with a focus on two problem points. fundamental, namely; (1) how is the disclosure of the story of Prophet Noah as in the Qur'an, (2) what educational values are contained in the story of Noah in the Qur'an. This research is library research which is classified as qualitative descriptive. The data and information obtained through several literatures were analyzed using content analysis, the approach used was the science of interpretation approach. The data is interpreted using the textual of the Qur'an, textual, linguistic, historical, systemic. The results of the study found that the value of monotheism referred to by Tauhid Rububiyah is to unite God in all actions and servitude. The value of sincerity is to empty oneself of heinous deeds. The value of patience is refraining from panic, holding the mouth from complaining a lot and controlling the limbs from doing things that are prohibited when exposed to disaster. The value of gratitude is; acknowledge all the gifts of Allah SWT by doing obedience and submission to Him. The value of rajā 'is eliminating feelings of fear so as not to return to sadness. The author also found from this study that the success of education in a student is not enough with the transformation of knowledge alone, but must be accompanied by internalizing the values on the character of these students with the right tools.